O descentramento e a desracialização do nacional: estado, relações étnico-raciais e ações afirmativas no Brasil - Medeiros, Priscila Martins (Universidade Federal de São Carlos, 2014)
In this text we examined the actions of the Brazilian government, in its different dimensions, compared to the social demands and academic debates on the ethnic-racial relations. Our thesis is that race and affirmative action with racial criteria categories intend to demarcate the nation and an important frontier in Brazilian scholarship on ethnic-racial relations, unraveling the processes of racialization present in the country's history. They intend to destabilize the nation, disarticulate and implode some of the pillars of the national discourse constructed throughout the twentieth century, namely: the Brazilian people - condensed in the discourse of mixed nationality; the myth of harmonious coexistence among ethnic and racial groups; and the notion that Brazilian racism would be harmless or residual. The central objective that guided this study was to understand the conceptual and ideological ruptures and transformations within the national-state in the course of antiracist struggles and achievements of rights. More specifically, we had the following objectives: to observe the concepts that guided the Brazilian intellectual production with regard to race relations in different historical moments; rescue the major elements present in the struggles of the Brazilian black movement in the highlighted period; understand which dialogues and which deadlocks present in the relationship between the state, the black movement and academia. In temporal terms rescued, first, some (social, political and theoretical) elements occurring in Brazil and elsewhere throughout the nineteenth and twentieth centuries and that assist us in understanding the current situation. Subsequently, we focus on the period stretching from the 1980s to the present day, when it opened a new scenario to think Brazilian racism due to reformatting of the Black Movement, the adoption of the Federal Constitution of 1988 and the emergence of affirmative action. The analysis is diachronic, since it prioritizes the processes, but also focuses attention on critical events, such as the Afonso Arinos Law; the Federal Constitution of 1988; the Durban Conference (2001); the National Curriculum Guidelines for the Education of Ethnic-Racial Relations and the Education of African-Brazilian and African History and Culture; decisions of the Supreme Court with respect to coordinates (2012), among others.
Keywords: Relações raciais; Estado; Nação; Ações afirmativas; Nation; Deracialization; Affirmative action; CIENCIAS HUMANAS::SOCIOLOGIA